THE USE OF SWEAR WORDS BY MALE AND FEMALE YOUTUBERS A Research Paper Submitted in Partial Fulfillment of the Requirement for Sarjana Sastra Degree - Nur Afifah Fauzziyah Fasya, - (2018)
Many previous studies have focused on the issue of swear words. However, these studies have not specifically focused on the use of swear words between male and female. Therefore, this paper aims to investigate the types of swear words used and the motives for using them by MR (male YouTuber) and TM (female YouTuber) in their YouTube videos. The data were collected from the utterances in the transcriptions of the two videos which contained swear words. To analyze the data, the theoretical framework proposed by Andersson and Trudgill (1990) was implemented to identify the types of swear words. Meanwhile, Andersson and Hirsch's framework (1985) was applied to investigate the motives influencing the use of swear words. The analysis was conducted through a qualitative method, which involved an identification and interpretation of swearing expressions used by the two YouTubers. The findings show that both male and female YouTubers used swear words in their YouTube videos. However, the use of swear words between them appears to be different in the types of the swear words used. Expletive, for instance, was the most frequent type used by the male YouTuber, while auxiliary is the most frequent type uttered by the female YouTuber. The differences are also found in terms of the motives for using those swear words. Psychological motives are the most predominant motives which underlie the use of swear words by the male YouTuber. Meanwhile, linguistic motives is the base motives for the female YouTuber to use swear words in her video. Based on the analysis, this finding gives several new perspectives on the issues of gender and swearing. With the rise of digital technology, it is evident that both MR and TM, for instance, are more accustomed to using swear words in public